Structural Characterization of Natural and Processed Zircons with X-Rays and Nuclear Techniques - Damonte, Laura C. (2017)
In ceramic industry, zircon sand is widely used in different applications because zirconia plays a role as common opacifying constituent. In particular, it is used as a basic component of glazes applied to ceramic tiles and sanitary ware as well as an opacifier in unglazed bulk porcelain stoneware. Natural zircon sands are the major source of zirconium minerals for industrial applications. In this paper, long, medium, and short range studies were conducted on zirconium minerals originated from Australia, South Africa, and United States of America using conventional and less conventional techniques (i.e., X-Ray Diffraction (XRD), Positron Annihilation Lifetime Spectroscopy (PALS), and Perturbed Angular Correlations (PAC)) in order to reveal the type and the extension of the regions that constitute the metamict state of zircon sands and themodifications therein produced as a consequence of the industrial milling process and the thermal treatment in the production line. Additionally, HPGe gamma-ray spectroscopy confirms the occurrence of significant levels of natural radioactivity responsible for metamictization in the investigated zircon samples. Results from XRD, PALS, and PAC analysis confirm that the metamict state of zircon is a dispersion of submicron disordered domains in a crystalline matrix of zircon.